The ilobolo Debacle in the Postcolonial Era: A South African Township Context - Mthembu, Ntokozo (International Journal of Criminology and Sociology, 2022)
This article uses historical evidence to track the invention of traditions in particular spheres of South African society since the late 1600s. Presently the ilobolo wedding ritual practice aligns with a colonially defined social transaction based on a monetary value system. This challenges the promise to “heal the divisions” brought about the colonial injustices of the past. The data were collected employing a case study, which enabled the researcher to collect qualitative and quantitative data. Theoretical thematic analysis was used to interpret the findings. The participants’ narrative revealed that prevailing socioeconomic conditions limit prospects for the development of an authentic family structure in the post-apartheid era in South Africa. In particular, it focuses on challenges such as the status of vulnerable men, a lack of access to natural capital (land) and a shift from the traditional establishment of receptive social relationships. It recommends that relevant stakeholders, such as traditional leaders, community members, and government agencies, should formulate strategies and policies to facilitate the restoration of the indigenous cultural values behind the principle of ilobolo and to remove the limits imposed by the consumerist tendencies that hover over the black African family structure.